(3GdSQWGf eQV bGHd ddTaGAs - (3QaGYj, eQhGfs ((3MdH (B[(3ShQjG(B]s (3TYGY ddfTQ h GdYdhes, 2003)
(3ChLO GdYdeGA WQbkG LOjOI aj YdGL GdCeQGV GdSQWGfjI ceG cTa HGdHMK h GdZMUGA Yf eYdheGJ LOjOI eajOI NGUI HJCKjQ GdYhGed GdeYjTjI h GdYGOGJ h GdLfS Ydi GfJTGQ GdeQV h Ydi CfhGYg eY JYOO h JbOe GdYdGLGJ EdG Cf GdcTa GdeHcQ Yf GdSQWGf Hbi GdYGed GdCge MJi jhefG gPG aj GdbVGA Ydi gPG GdeQV(B. (3h gPG GdYGed HGdJMOjO jYJeO Ydi KbGaI UMjI h eYQaI Hcd eG jJYdb HgPG GdeQV h NGUI GdhYj GdcGed ddCYQGV GdeHcQI dgPG GdeQV GdeDOjI Edi GdcTa GdeHcQ Yfg(B. (3h HGdJGdj dJbOje CaVd SHd GdTaGAs
1 22
Keywords: (3GdSQWGfs -- (3JTNjUs; (3GdSQWGfs -- (3eQVs